The Influence of Technology in the Development of Information Systems on the Field of Management Accounting - Syamsuddin, Syamsuddin; Permana, Nalendra Bhayu; Sundari, Sri; Nur, Hamzah Fansyuri (International Journal of Business and Applied Economics, 2024)
The purpose of this article is to examine the impact of advancements in information technology on management accounting. The study employs descriptive qualitative methods and a literature review. Findings indicate that technological progress has led to significant transformations in the business sector. Various information systems now incorporate emerging technologies, including electronic data processing systems, data processing systems (DPS), decision support systems (DSS), management information systems (MIS), expert systems (ES), and accounting information systems (AIS). Information technology development also affects management accounting, as it generates information essential for planning, control, and decision-making processes. Consequently, the influence of information technology on management accounting can either benefit or challenge businesses.